PENGARUH UMUR PANEN TERHADAP PERFORMA PERTUMBUHAN, BIOMASSA DAN PRODUKTIVITAS RUMPUT LAUT Kappapycus alavarezii DI TELUK WAWORADA - Ardiansyah Ardiansyah; Neri Kautsari; Dwi Mardhia; Yudi Ahdiansyah; Syamsul Bachri; Didit Abdillah (Program Studi Budidaya Perairan Universitas Mataram, 2022)
Waworada Bay is a water in Bima Regency which has long been used by some people for seaweed cultivation. Currently, seaweed farmers do not know the exact harvest period. This causes differences in the harvest period between farmers. So far, research on the harvest period in Waworada Bay is not yet available. The experiments aimed to assess the ideal period for harvest among the different growth periods (35, 45, and 55 days). This research was conducted in Waworada Bay, Langgudu District, Bima Regency, West Nusa Tenggara from November 2021 to January 2022. Observation variables were absolute growth, growth rate, wet and dry biomass, productivity and water quality (temperature, dissolved oxygen, salinity, pH, brightness, current). The seaweed cultivation method uses the longline method. The results showed that the highest absolute growth was found in the 55-day harvest period (115.70±1.71 g) and the lowest was in the 35-day harvest period (55.10±6.62 g). There was a significant difference in absolute growth between treatments. The growth rate was not significantly different between treatments with a value range of 1.09±0.24 to 3.55±1.39%day-1. Wet biomass ranged from 10,022±397.22 g 12m-1 (harvest period 55 days) to (6.306±149.92 g 12m-1) (harvest period 35 days). Dry biomass ranged from 670±34.12 g 12m-1 to 1.016±53.78 g 12m-1. Productivity ranges from 0.04 to 0.07 g dry weight m−2 days−1. The average water quality values are temperature 32.40 0C, dissolved oxygen 5.84 mg l-1, salinity 32 ppt, pH 7.30, brightness 2.50 m and current 14 cm sec-1.